Evaluating soil phosphorus tests and nutrient limitations in Mediterranean pastures - Margarida Arrobas; Soraia Raimundo; Almeida Sawimbo; Nuno Rodrigues; Marjan Jongen; Ricardo F. M. Teixeira; Tiago Domingos; Manuel Ângelo Rodrigues (Universitas Sebelas Maret, 2025)
Reliable phosphorus (P) fertilization guidelines for Mediterranean pastures remain uncertain due to inconsistent soil testing methods, the complexity of mixed-species systems, and the neglect of other limiting nutrients. This study primarily aimed to identify reliable soil P tests and secondarily to explore potential nutrient limitations by assessing seven acidic Portuguese soils under Mediterranean conditions using subterranean clover (Trifolium subterraneum) and ryegrass (Lolium multiflorum) as model species. Five P extraction methods (Egner-Riehm, Olsen, Bray II, Mehlich I, and anion exchange resin) were compared alongside a pot experiment with clover, ryegrass, and their mixture. Biomass production, plant nutritional status, and soil–plant relationships were used to assess nutrient availability and plant response. The Egner-Riehm method proved the most reliable, showing linear correlation with the resin method (R² = 0.89), widely regarded as the best indicator of soil P bioavailability. P availability was therefore not a limiting factor for biomass production. The lowest soil P content (54 mg kg⁻¹ P₂O₅, Egner-Riehm) was close to the medium threshold (50–100 mg kg⁻¹), yet plant growth indicated adequacy. In contrast, nitrogen (N) emerged as the main growth constraint, and boron (B) deficiency further restricted clover performance, confirming additional nutritional imbalances. A linear relationship between soil and tissue B supported its association with DMY, and tissue B levels were below sufficiency thresholds. Overall, in acidic Portuguese soils under Mediterranean conditions, soil P was adequate, whereas N and B acted as key constraints to productivity. These findings support more accurate and efficient fertilization strategies for Mediterranean pastures.